Educational Development and Skills in Clean Mobility at IFP School - El Ganaoui Mourlan Ouafae; Zein Ismail; Dulbecco Alessio; Miliani El-Hadj; Nunez Claude (EPJ Web of Conferences)
In this paper, we explore the innovative academic initiatives at IFP School, France, designed to equip master’s degree students with essential skills for advancing clean mobility. We highlight the dynamic evolution of our educational programs in response to the global energy transition, providing detailed insights into course structures that focus on sustainable mobility, electrification, and smart grids. Our curriculum is uniquely integrated with practical training methods, including virtual reality, laboratory experiments, and extensive industry collaborations. This comprehensive approach ensures that our graduates are well-prepared to meet the current and future demands of the rapidly evolving automotive and energy sectors.